PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN PROMOSI TERHADAP LOYALITAS PELANGGAN (Studi Kasus pada Konsumen Larissa Aesthetic Center Semarang) - Yunita Kartikasari; Apriatni Endang Prihatini; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2015)
The increasing growth of beauty clinics and offers a variety of benefits for fulfilling the society needs in field of beauty and skin health. Larissa Aesthetic Center is one of the beauty clinics which try to meet these needs by the use of natural raw materials, so that the company's goal is customer loyalty can be increased. Larissa Aesthetic Center Semarang has decreased the number of active members in 2011 to 2013.This type of research is using explanatory research. Data collection techniques through questionnaires using purposive sampling with a sample of 100 consumers.Data were analyzed through the validity, reliability, crosstab, correlation, coefficient of determination, simple linear regression, multiple linear regression, t test and F test using SPSS for Windows Version 17. The results show that product quality, service quality and promotion have partial and simultaneous effect to customer loyalty. Product quality provides the most effect on customer loyalty.The suggestions that can be given in this research are explain and provide more information to customers about how storage products, serve customers well and prioritize customer needs.